PROBLEMATIKA GURU AQIDAH AKHLAK DALAM MENANAMKAN KARAKTER SISWA DI MADRASAH ALIYAH SALAFIYAH SYAFI’IYAH TEBUIRENG JOMBANG - Uday, Masrufi Muhammad; Ilahiyah, Iva Inayatul (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2025)
Abstract: Character building is a crucial part of students’ personality development and should be the main focus in the education system. In this case, Aqidah Akhlak teachers play a crucial role because they are tasked with guiding and practicing Islamic values to students. This study aims to identify: 1) the challenges faced by Aqidah Akhlak teachers at MASS Tebuireng Jombang, 2) the character of students at the madrasah, and 3) the obstacles faced by teachers in creating student character. The study was conducted using a qualitative method with a case study approach. Data collection techniques included observation, interviews, and documentation. Informants consisted of the principal, Aqidah Akhlak teachers, and students. Data analysis was carried out through source triangulation to ensure the validity of the information. The results of the study showed that teachers face various challenges, such as the influence of a less supportive social environment, differences in intelligence levels between students, and limitations in implementing interesting and innovative learning methods. Nevertheless, teachers continue to strive to develop more creative learning approaches and build good communication with students in order to instill Islamic values. To support the success of character education, a more structured strategy and cooperation from all parties involved are needed.